Investigation of hepatitis A outbreak in district of Manjung, Perak, Malaysia, October 2012 - Faudzi Ahmad Yusoff; Rusdi Abdul Rahman; Ling He May; Suzana Binti Budart; Lokman Hakim Sulaiman (World Health Organization Regional Office for the Western Pacific, 2015)
Abstract Background: In September 2012, 10 cases suspected to be hepatitis A were notified to the Manjung District Health Department. An investigation was conducted to identify the possible mode of transmission, source of the outbreak and to recommend prevention and control measures. Methods: A case was a person with acute illness with discrete onset of symptoms and jaundice or elevated serum aminotransferase levels in September 2012 in the Manjung District. We conducted a case-control study and environmental assessments of processing plants and food premises. Results: There were 78 confirmed cases of hepatitis A; an attack rate of 3.1 per 10 000 population. Multiple logistic regression showed that being male (odds ratio [OR]: 18.4 [5.13-65.9]; P < 0.001) and drinking toddy at processing place A (Adjusted OR: 2.70 [1.17-6.25]; P < 0.05) were associated with being a case. Environmental investigations of this and one other processing place found them to be unhygienic, and the pH of the toddy was at levels that encouraged growth of hepatitis A virus. Conclusion: Toddy was possibly the primary source of this outbreak based on both epidemiological and environmental results. Both toddy preparation places and several food premises were closed as a result of this investigation.